Use of time in couple relationships and in the exercise of motherhood and fatherhood in Costa Rica: a critical analysis from a sociological perspective - Salazar Miranda, Adriana (2022)
The objective was to develop an analysis of the existing asymmetries and gaps in the use of time between men and women, both in their relationship as a couple and in the exercise of motherhood and fatherhood, which means reviewing, on the one hand, the of daily tasks linked to unpaid domestic work, the care and upbringing of minors and, on the other hand, the free time dedicated to recreational, sports and personal care activities. The theoretical framework takes up the contributions of sociology and sexual political economy, where romantic love, idyllic motherhood and motherhood as punishment are problematized, in contrast to contemporary trends that reflect on the experience of pleasant motherhood. In methodological terms, it corresponds to a bibliographical research, where information collected by the National Survey of Time Use (abbreviated as ENUT from its original Spanish name, Encuesta Nacional de Uso del Tiempo) 2017 and other studies developed at the national level were used. It is verified that a social and sexual contract persists within couple relationships, which places women in a disadvantaged situation regarding the use of the most valuable resource: time. Since there are clear asymmetries between both sexes regarding days of unpaid work, care and upbringing. This is based on the romantic idea of love, which works to extract time and vital energy from women, proving that there is a supervised but little accompanied maternity; finally, some reflections are offered on the exercise of pleasant motherhood and, therefore, of responsible parenthood.